2013
DOI: 10.3989/gya.108312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary inclusion of lampante olive oil on milk and cheese fatty acid profiles of ewes

Abstract: RESUMENEfecto de la inclusión de aceite de oliva lampante en la dieta de ovejas sobre el perfil de ácidos grasos de leche y queso El objetivo de este estudio fue evaluar el efecto de la inclusión de aceite de oliva lampante en la dieta de ovejas sobre el perfil de ácidos grasos de leche y queso. Nueve ovejas fueron utilizadas en un diseño de CuadradoLatino 3 × 3. Las dietas fueron suplementadas con 0 (control; T0), 36 (T1) y 88 (T2) g de aceite de oliva lampante por kg de materia seca de alimento. La ingesta, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
5
6
0
2
Order By: Relevance
“…According to Turan et al (2007), lower AI and TI translate into more anti- Fatty acids profile atherogenic FAs and better disease prevention profiles. Nevertheless, it should be remarked that the determined levels are in accordance with the ranges previously reported by other researchers for ewe, goat and cow cheeses (Aguilar et al, 2014;Cabiddu et al, 2006;G omez-Cortés et al, 2009;Oliveira et al, 2015;Rodrigues et al, 2012;Taboada et al, 2015;Vargas-Bello-Pérez et al, 2013a, 2013b. Moment of manufacturing presented low AI and TI and the R(v -6)/R(v -3) values were below recommended level (less than 4.0) thus differences observed might be attributed to differences in animal's feed (location in de region) and to the producer.…”
Section: Lipid Quality Indices: Influence Of Origin and Moment Of Prosupporting
confidence: 92%
See 1 more Smart Citation
“…According to Turan et al (2007), lower AI and TI translate into more anti- Fatty acids profile atherogenic FAs and better disease prevention profiles. Nevertheless, it should be remarked that the determined levels are in accordance with the ranges previously reported by other researchers for ewe, goat and cow cheeses (Aguilar et al, 2014;Cabiddu et al, 2006;G omez-Cortés et al, 2009;Oliveira et al, 2015;Rodrigues et al, 2012;Taboada et al, 2015;Vargas-Bello-Pérez et al, 2013a, 2013b. Moment of manufacturing presented low AI and TI and the R(v -6)/R(v -3) values were below recommended level (less than 4.0) thus differences observed might be attributed to differences in animal's feed (location in de region) and to the producer.…”
Section: Lipid Quality Indices: Influence Of Origin and Moment Of Prosupporting
confidence: 92%
“…Indeed, low values of AI, TI and R(v -6)/ R(v -3) are highly desirable as well as higher values of DFA, SCFA and MCFA. Several researchers reported the AI values for different types of ewe cheese (0.84 for supplemented diet to 5.57 for no supplemented diets) showing that sheep diet supplementation allowed a decrease of the AI values (Cabiddu et al, 2006;G omez-Cortés et al, 2009;Vargas-Bello-Pérez et al, 2013a, 2013b). For commercial ewe cheese, Aguilar et al (2014) found mean AI values of 2.33-2.63, TI values varying within 2.81-3.10 and, R(v -6)/R(v -3) ratios ranging between 3.79 to 6.45, which were similar to those previously reported in the literature for ewe cheeses.…”
Section: Lipid Quality Indices: Influence Of Origin and Moment Of Promentioning
confidence: 99%
“…It is known that in small ruminants, the degree of FA saturation of lipid sources will influence animal performance [ 3 ], milk composition [ 14 ] and milk FA profile [ 15 , 16 ]. In fact, in goat mammary epithelial cells, saturated and unsaturated long-chain FAs exert differential expression of genes related to lipid metabolism [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios (21,23) señalan que la suplementación de aceites vegetales mejora la producción de leche en ovejas y cabras debido a que aumenta el nivel de energía en la dieta. También se ha reportado que la inclusión de aceites vegetales en dietas formuladas isoenergética e isoprotéicamente provoca que se incluya un mayor nivel de forraje (24,25) . Lo anterior puede promover una interacción positiva entre el aceite vegetal adicionado y la mayor cantidad de forraje de las dietas para incrementar la producción de ácidos grasos volátiles, principalmente de acetato y butírico, los cuales se relacionan con una mejor secreción láctea en ovejas (14,26) .…”
Section: Producción Y Composición Del Calostrounclassified